Chemical profile and antifungal activity of essential oil from the flower of Bauhinia rufa (Bong.) Steud. - Menezes Filho, Antonio Carlos Pereira de; Sousa, Wendel Cruvinel de; Silva, Jaquelline Lemos; Cruz, Rafael Martins da; Silva, Adrielle Pereira da; Castro, Carlos Frederico de Souza (Brazilian Journal of Science, 2022)
Bauhinia rufa is one of the species found inhabiting the Cerrado domain. Annually this plant species presents flowering with a light sweet aroma. The objective of this work was to evaluate the chemical profile and antifungal activity of the essential oil of B. rufa flowers on Sclerotinia sclerotiorum, Coletotrichum gloeosporioides and Aspergillus flavus. Flowers were collected in the early hours of the morning, being sent to the laboratory for extraction and yield of essential oil by the Clevenger-type system. The chemical profile of the essential oil was obtained by gas chromatography with mass detector (GC-MS), and for antifungal activity, sequences of concentrations 100, 50, 25, 12.5; 6.25; 3.13 and 1.56 µL mL-1 on strains of S. sclerotiorum, C. gloeosporioides and A. flavus. The essential oil of B. rufa showed a yield of 0.05%, 28 compounds identified, the majority being Myrcene (8.27%), O-Cymene (31.14%), 1,2-dimethyl-4-ethyl-benzene (13.08%), Trans-Pinocarveol (12.55%) and Kryptone with (8.94%). The antifungal activity showed the best results for S. sclerotiorum and C. gloeosporioides where they exhibited fungistatic activity between 100 and 54.84% at all concentrations. For A. flavus, the best inhibition concentrations were observed between 100 to 25 µL-1 with 100%, and in the lowest concentrations of 12.5 and 6.25 µL-1 with 40.55 and 10.08%, no inhibition was observed at concentrations 3.13 and 1.56 µL-1. The essential oil of B. rufa showed richness in chemical compounds and effective fungicidal action.